2016
DOI: 10.5935/abc.20160049
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensives' Knowledge About High-Sodium Foods and Their Behavior

Abstract: BackgroundIn Brazil, the prevalence of systemic arterial hypertension (SAH) is approximately 30% of the total population. In 2010, SAH was the cause of death of about 9.4 million people worldwide. A healthy dietary pattern is important to maintain proper blood pressure levels and, consequently, disease control.ObjectivesTo describe the knowledge and practices of hypertensive patients cared for at a public hypertension outpatient clinic, and its relationship with high-sodium food.MethodsWe applied a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
(13 reference statements)
0
5
0
5
Order By: Relevance
“…Reading food additional information and nutritional labels are known as core behavior of dietary salt. 10,18 The findings indicated only a limited number of participants always considering packaged indication. About one-fifth for the CHT group and onethird for the UHT group were never paying attention of food indication.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reading food additional information and nutritional labels are known as core behavior of dietary salt. 10,18 The findings indicated only a limited number of participants always considering packaged indication. About one-fifth for the CHT group and onethird for the UHT group were never paying attention of food indication.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies in American countries found similar findings. 9,18,19 Information concerning on appropriate understanding of recommended salt intake and the importance of salt reduction program are necessary for successful treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Não obstante, a maioria dos entrevistados relatou que segue dieta nutricional prescrita por profissionais de saúde. Estudo realizado em Porto Alegre, que avaliou o conhecimento das pessoas com HA sobre os alimentos ricos em sódio, resultou em um conhecimento insuficiente, considerando que os sujeitos possuem acompanhamento regular em ambulatório especializado, apontando a necessidade de orientações nutricionais e incentivo aos hábitos alimentares saudáveis (21) . Nesse aspecto, as ações assistenciais providas pela equipe de enfermagem pelos profissionais de nutrição, que atuam no Núcleo de Apoio à Saúde da Família (NASF), com ações de avaliação de uma dieta adequada e prescrição de um plano dietético, de caráter individual e efetivo à população assistida por sua equipe e que também é sugerida pelo MS. Estas ações necessitam ser definidas a partir da gestão de caso, com a equipe médica responsável pelo acompanhamento e avaliação dos resultados (20,22) .…”
Section: Discussionunclassified
“…In order to promote healthier eating habits and improve self-care regarding CNCD, it is important for the population to gain knowledge about food and nutrition, [4][5][6] especially those related to healthy food choices and nutritional recommendations. 7 Several studies have found a relationship between dietary knowledge and obesity, [8][9][10][11] as well as nutritional status.…”
Section: Introductionmentioning
confidence: 99%